How do translators handle (near-) synonymous legal terms? A mixed-genre parallel corpus study into the variation of EU English-Polish competition law terminology - Biel, Łucja; Koźbiał, Dariusz (Estudios de Traducción, 2020)
Terminological variation, i.e. synonymy at the term level, is regarded as a recurrent problem in EU law. Working with a parallel-comparable corpus of EU English-Polish legislation, soft law and judgments in the area of competition, this study explores how source-language synonymy is handled in translation across institutional genres. The findings show that synonyms may be reflected symmetrically or asymmetrically, with variation being eliminated, partly reduced, mirrored, or increased in translation. It is quite frequent for translators to introduce additional variation and cross-variation. This is affected by: genre, source and target asymmetries, complexity of a semantic field, low termness and microdiachronic shifts. The study confirms that synonymy is one of the causes of variation in translation and calls for more conceptual clarity at the drafting stage.